Karakteristik dan Diagnosis Psikiatri pada Pasien Percobaan Bunuh Diri di RSUP Sanglah - Ni Wayan Pradiumnati Pritiariesti; Ni Ketut Sri Diniari (Universitas Udayana, 2017)
Suicide attempt is a form of deliberate self-harm with the purpose of death, but it does not end with death. Self-harm representspsychological difficulties and there are several risk factors related with suicide attempt. The purpose of this study is to know theproportion of characteristics and psychiatric diagnosis in suicide attempt patients at RSUP Sanglah. Research is done at Bagian/SMF Psikiatri RSUP Sanglah from 1st June 2013 until 31st May 2014. The method of this study is cross-sectional descriptive to knowthe proportion of psychiatric diagnosis in suicide attempt patients. The data is secondary data that consists of suicide attemptpatients aged 11 to 60 years old at Department of Psychiatry RSUP Sanglah that fulfill the requirements of inclusion. From91 suicide attempt samples, most of them are diagnosed with psychiatric disorders with total count of 78 patients (85.7%).The highest proportion of psychiatric diagnosis that is obtained from this study is depression (36.3%). Most of suicide attemptpatients are women, aged 21 to 30 years old, last educated in senior high school, unmarried, and employed. Suicide attemptspatients are mostly women, aged 21 to 30 years old, last educated in senior high school, unmarried, and employed. Most ofsuicide attempt patients have psychiatric diagnosis, especially depression.